2008
DOI: 10.1590/s1516-89132008000500012
|View full text |Cite
|
Sign up to set email alerts
|

Duration of the pre-settlement period of the mangrove crab Ucides cordatus (Decapoda: Ocypodidae) under laboratory conditions

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Adults of Ucides are most likely responsible for the construction of larger tunnels (Warner 1969, Branco 1991, Ventura et al 2008. Some paths seem to be only enlarged gaps between oyster clumps and secondary roots.…”
Section: Communal Burrows Structurementioning
confidence: 99%
“…Adults of Ucides are most likely responsible for the construction of larger tunnels (Warner 1969, Branco 1991, Ventura et al 2008. Some paths seem to be only enlarged gaps between oyster clumps and secondary roots.…”
Section: Communal Burrows Structurementioning
confidence: 99%
“…The resulting techniques produced more than 1 million young forms in the megalopae phase per reproductive season (Silva et al, 2009). During this period, several issues related to this technology were investigated, such as settlement behavior (Ventura et al, 2008) and predation of megalopae by fishes (Costa et al, 2009) and by other crab species after release into the environment (Ventura et al, 2010).…”
Section: Comparação Morfométrica Entre Megalopas Do Caranguejo Do Manmentioning
confidence: 99%
“…As observed with regard to Callinectes sapidus and Portunus trituberculatus (SECOR et al, 2002), success in the use of immature portunid crabs reared in the laboratory for restocking purposes depends largely on their age at the moment of release into the natural environment. Recent studies have suggested that the release of juveniles of the mangrove crab U. cordatus, might also be more effective in view of their putative reduced susceptibility to predation by fish and their greater ability to compete with crabs of other species (VENTURA et al, 2008).…”
Section: Introductionmentioning
confidence: 99%